Decreasing Poly(ADP-Ribose) Polymerase Activity Restores ΔF508 CFTR Trafficking - Anjos, Suzana M.; Robert, Renaud; Waller, Daniel D.; Zhang, Donglei; Balghi, Haouaria; Sampson, Heidi M.; Ciciriello, Fabiana; Lesimple, Pierre; Carlile, Graeme; Goepp, Julie; Liao, Jie; Ferraro, Pasquale; et al. (Frontiers in Pharmacology, 2012)
Most cystic fibrosis is caused by mutations in CFTR that prevent its trafficking from the ER to the plasma membrane and is associated with exaggerated inflammation, altered metabolism and diminished responses to oxidative stress. PARP-1 is activated by oxidative stress and causes energy depletion and cell dysfunction. Inhibition of this enzyme protects against excessive inflammation and recent studies have also implicated it in intracellular protein trafficking. We hypothesized that PARP-1 activity is altered in CF and affects trafficking and function of the most common CF mutant ΔF508 CFTR. Indeed, PARP-1 activity was 2.9-fold higher in CF (ΔF508/ΔF508) human bronchial epithelial primary cells than in non-CF cells, and similar results were obtained by comparing CF vs. non-CF bronchial epithelial cell lines (2.5-fold higher in CFBE41o- vs 16HBE14o-, P<0.002). A PARP-1 inhibitor (ABT-888, Veliparib) partially restored CFTR channel activity in CFBE41o- cells overexpressing ΔF508 CFTR. Similarly, reducing PARP-1 activity by 85% in ileum from transgenic CF mice (Cftrtm1 Eur) partially rescued ∆F508 CFTR activity to 7% of wild-type mouse levels, and similar correction (7.8%) was observed in vivo by measuring salivary secretion. Inhibiting PARP-1 with ABT-888 or siRNA partially restored ΔF508 CFTR trafficking in cell lines, and most ΔF508 CFTR was complex glycosylated when heterologously expressed in PARP-1-/- mouse embryonic fibroblasts. Finally, levels of the mature glycoform of CFTR were reduced by peroxynitrite, a strong activator of PARP-1. These results demonstrate that PARP-1 activity is increased in CF, and identify a novel pathway that could be targeted by proteostatic correctors of CFTR trafficking.